Zig Zag Book Media Based on Augmented Reality “BERUANG” on Mathematics Learning of Classroom Building Material V Elementary School - Amelia Nurhaliza Putri; Elok Fariha Sari (Jurnal Penelitian dan Pengembangan Pendidikan, 2025)
The learning process is still less active, and students' interest in learning spatial figures is relatively low. One of the causes is the limited use of interesting learning media. This study aims to develop and test the feasibility, practicality, and effectiveness of the Augmented Reality-based Zig Zag Book learning media named "BERUANG". This study uses the Research and Development (R&D) method with the ADDIE development model approach. The subjects of this study consisted of 27 students. Data collection methods in this study were observation, questionnaires, interviews, and tests. The instruments used for data collection include material validation sheets, media validation sheets, pretests, posttests, instruments to measure media effectiveness, and response questionnaires from educators and students. Data analysis used qualitative, quantitative descriptive analysis, and inferential statistics (t-test and n-gain). The results showed that material validation reached 95%, while media validation obtained 87.5%. In terms of practicality, the student response questionnaire showed that the level of media practicality reached 97%. Based on these findings, it can be concluded that the Zig Zag Book media based on Augmented Reality can improve students' mathematics learning outcomes. The implications of the research are that the media developed is suitable for use as supporting media.